Choosing a Career Path: Moving Beyond the Challenges of Autism Spectrum Disorder - Spencer, Vicky G.; Cesard, S. Lynn (Journal of the American Academy of Special Education Professionals, 2022)
Autism Spectrum Disorder (ASD) is a developmental disability that can cause significant social, communication and behavioral challenges. It is estimated that 1 in 54 children has been diagnosed with ASD (Center for Disease Control and Prevention (CDC) 2020). One area of concern for some parents is food selectivity which can be a common problem among individuals with ASD and often continues into adulthood. For this in-home case study, 13-year-old Michael has ASD, and his underlying cognitive rigidity and sensory issues were impeding his career goal of becoming a dessert chef. Prior to the intervention, Michael ate a very restrictive diet, refusing all fruit, beef, fish, and vegetables. The specific intervention for addressing Michael’s food selectivity issues included goal-setting, providing choice-making opportunities, developing and implementing a plan. The results suggest that using choice as an antecedent manipulation may be an effective method for the treatment of food selectivity.